PELATIHAN KERAJINAN TANGAN DALAM UPAYA PEMULIHAN PEREKONOMIAN MASYARAKAT KORBAN ERUPSI SEMERU DI DESA SUPITURANG KECAMATAN PRONOJIWO KABUPATEN LUMAJANG - Ansori, Ansori; Soffiyuddin, M.; AR, Zaini Tamin; Mawardi, Imam; Rohmah, Naily (Jurnal Abdi Insani, 2025)
In the field, most assistance provided to victims of the Mount Semeru eruption has taken the form of physical aid, such as basic necessities, cash, clothing, and construction materials. However, educational support, such as training and counseling, has been quite rare. Therefore, the craft training program conducted by the Community Service Institute (LPPM) of STAI YPBWI Surabaya is highly relevant for the eruption victims. This initiative serves as a bridge for the economic recovery of affected communities. This community service aims to implement craft training for Semeru eruption victims, enabling them to create economically valuable products and explore efforts for economic recovery among those impacted in Supiturang Village, Pronojiwo District, Lumajang. This project employs Participatory Action Research (PAR), actively involving the community in the training and skill development processes. Through PAR, the eruption victims do not merely serve as research objects but play an active role as subjects directly engaged in each stage, from needs identification and planning to program implementation. The craft training for Semeru eruption victims enhances participants’ knowledge and skills in creating marketable products. The economic impact is evident in participants' ability to independently produce and sell products, though marketing difficulties remain a significant challenge. The availability of basic materials supports the training, although a shortage of labor hinders large-scale production. Sustainable solutions involve business mentoring, strengthening marketing networks, and collaboration to support the workforce and fortify the local economic ecosystem. This training program not only imparts technical skills but also paves the way for sustainable economic recovery and the development of local potential post-disaster. Continued perseverance is needed to educate residents on marketing their products in local markets, schools, and tourist areas.